Ex vivo normothermic perfusion for quality assessment of marginal donor kidney transplants. Issue 11 (27th August 2015) - Hosgood, S A; Barlow, A D; Hunter, J P; Nicholson, M L
Abstract: Background: A significant proportion of kidneys procured for transplantation are discarded because of concerns about their suitability. In this study ex vivo normothermic perfusion (EVNP) was used as a quality assessment device before renal transplantation. Methods: Seventy-four human kidneys deemed unsuitable for transplantation following retrieval underwent 60 min of EVNP with an oxygenated red cell-based solution at 36°C. Receiver operating characteristic (ROC) curves were used to identify thresholds of renal blood flow and urine output. These thresholds and a grading of macroscopic appearance were incorporated into an EVNP assessment score (highest quality, 1; lowest, 5). This was applied to a series of 36 kidneys transplanted after EVNP. Results: In the discarded kidney series, 60 (81 per cent) scored 1–4 and 14 (19 per cent) scored 5. Although none of these kidneys was transplanted, those with a score from 1 to 4 were considered suitable for transplantation. In the 36 transplanted kidneys, the score ranged between 1 and 3 (score 1, 17; score 2, 11; score 3, 8). All of these kidneys were transplanted without any complications or primary non-function. The delayed graft function rate was 6 per cent (1 of 17) in kidneys scoring 1, 0 per cent (0 of 11) in those scoring 2 and 38 per cent (3 of 8) in those scoring 3 ( P = 0·024). The mean(s.d.) estimated glomerular filtration rate at 12 months was 51(16), 63(15) and 38(21) ml in kidneys scoring 1, 2 and 3 respectively ( P = 0·015). Conclusion: EVNP combined with a simple scoring system is an innovative technology for pretransplant assessment of kidney quality and acceptability for transplantation. This study suggests that a high percentage of retrieved kidneys are being discarded unnecessarily. Abstract : Maximizes kidney use